PENGARUH MOTIVASI BELAJAR DAN DUKUNGAN ORANG TUA TERHADAP HASIL BELAJAR KELISTRIKAN OTOMOTIF - Sugeng Pramudibyo; Esta Larosa; Hasanuddin (Steam Engineering, 2022)
This study aims to analyze the effect of learning motivation and parental support on the learning outcomes of automotive electrical subjects in class XI automotive light vehicles at the Walisongo 2 Gempol Vocational High School. This study uses a descriptive correlational research design. The data from this study were obtained from a questionnaire given to students for the variables of learning motivation and parental support, while the data on student learning outcomes in automotive electrical subjects was obtained by documentation. The method in this research is descriptive quantitative correlation. Based on the results of the research and discussion that have been described, it can be concluded that there is a positive relationship between student learning motivation (X1) and student learning outcomes in the automotive electrical training subject of SMK Walisongo 2 Gempol (Y) students, where the better the student's motivation, the better. Student learning outcomes. There is a positive relationship between parental support (X2) and student learning outcomes in the automotive electrical training subject of Walisongo Walisongo 2 Gempol Vocational High School (Y), where the better the parental support, the better student learning outcomes. There is a positive relationship between learning motivation (X1), parental support (X2) with student learning outcomes in automotive electrical training (Y), these variables together relate to student learning outcomes at Walisongo Walisongo 2 Gempol Vocational High School.